Endocrine Resistance in Hormone Receptor Positive Breast Cancer–From Mechanism to Therapy - Rani, Aradhana; Stebbing, Justin; Giamas, Georgios; Murphy, John (Frontiers in Endocrinology, 2019)
The importance and role of the estrogen receptor pathway has been well documented in both breast cancer development and progression. The treatment of choice in women with metastatic breast cancer is classically divided into a variety of endocrine therapies, 3 of the most common being: selective estrogen receptor modulators, aromatase inhibitors and selective estrogen receptor down-regulators. In a proportion of patients, resistance develops to endocrine therapy due to a sophisticated and at times redundant interference, at the molecular level between the estrogen receptor and growth factor. The progression to endocrine resistance is considered to be a gradual, step-wise process. Several mechanisms have been proposed but thus far none of them can be defined as the complete explanation behind the phenomenon of endocrine resistance. Although multiple cellular, molecular and immune mechanisms have been and are being extensively studied, their individual roles are often poorly understood. In this review, we summarize current progress in our understanding of estrogen receptor biology and the molecular mechanisms that predispose and determine endocrine resistance in breast cancer patients.